ABSORBENCY CHARACTERISTICS OF PESHTAMALS: TRADITIONAL TURKISH WOVEN CLOTHES - KESKIN Reyhan; PALAMUTCU Sema; KARA Serkan (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2014)
Absorbency of textiles is defined as the ability of taking in a fluid in the manner of a sponge. Absorbency is required for comfort properties in so me clothes such as sportswear and underwear clothing, for drying properties in napkins, towels and bathrobes, for health concerns in some medical textiles such as bandages, gauze and absorbent cotton, and for cleaning properties in washclothes and mops. In this study five different fabric samples (three woven 100% cotton fabrics A, B and P respectively at plain, twill, and peshtamal weaving patterns and two 100% cotton terry towels T1 and T2) were tested. The absorbency properties of the samples were evaluated according to the droplet test, sinking time test and wicking height tests (pottasium chromate test). Peshtamal samples showed better absorbency results than plain and twill weaves and lower but close results to towel samples according to the droplet test, sinking time test and wicking height tests. The absorbency properties of peshtamals showed results close to towel samples. The void content of peshtamals is higher than plain and twill samples but closer and lower than towel samples. The good absorbency results of peshtamals might be due to the void content of peshtamals which is higher than plain and twill samples but closer and lower than towel samples. Peshtamals which are good in absorbency and light in weight might be used widespreadly in daily life for their high absorbency, and on travel for weight saving purposes.